Engineering Social Memory of Post-conflict societies: Case Study of Iraq and Lebanon (قضايا سياسية, 2022)
Although the Iraqi and Lebanese societies have witnessed at certain periods, (Iraq after 2003 and Lebanon for the period 1975-1990), societal, identity, religious, doctrinal and national conflict, in which social memory was exploited and employed negatively, increasing conflict intensity and the depth of societal rift, however, the study sample in both societies revealed a deep desire and a great willingness to renounce the memory that fuels conflict, particularly it revealed that the past, despite its importance, yet it is not recalled as a past but for the sake of taking advantage of its lessons, in order not to repeat them in the future. So, there is a desire to remember the happy past away from the painful one. In conclusion, the study has revealed the possibility of dismantling and re-constructing social memory, in a way that establishes an integrated unified society that transcends the negative conflict-fuelling past and focuses on a future that is framed by a positive relationship within the framework of citizenship.